1999
DOI: 10.1161/01.str.30.5.939
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cognitive Hemispheric Lateralization by “Functional” Transcranial Doppler Cross-Validated by Functional MRI

Abstract: Background and Purpose-Changes of blood flow velocity in the right and left middle cerebral artery (MCA) induced by cognitive demands are detectable by means of "functional" transcranial Doppler sonography (fTCD). Functional MRI (fMRI) is an alternative method for mapping brain activity. The purpose of this study was to determine whether fTCD can detect hemispheric lateralization and to cross-validate fTCD with fMRI. Methods-Bilateral continuous MCA monitoring of 14 healthy, right-handed subjects with TCD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 35 publications
0
34
0
2
Order By: Relevance
“…The MCA territory supplies about 80% of blood received by the cerebral hemispheres (Toole, 1984). In relation to site-specific functional localization, TCD could be considered a good test in series with other imaging modalities such as functional magnetic resonance imaging (fMRI) (Schmidt et al, 1999).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCA territory supplies about 80% of blood received by the cerebral hemispheres (Toole, 1984). In relation to site-specific functional localization, TCD could be considered a good test in series with other imaging modalities such as functional magnetic resonance imaging (fMRI) (Schmidt et al, 1999).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Studies with TCD have been cross-validated by functional MRI (Schmidt et al, 1999), and reproducibility assessed (Knecht et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that CBF increases during brain activation and even exceeds the values achieved before CEA in patients with ICA steno-occlusive disease, 3,27 this effect could not be found in patients with a stenosis level of Ն90%. This seemingly paradoxic result may be due to patients with highgrade ICA stenosis (Ն90%) having a reduced CPP, which stimulates cerebral autoregulation and leads to a vasodilation with concomitant CBF increase under the resting state.…”
Section: Degree Of Stenosismentioning
confidence: 87%
“…Since its introduction, FTCD has substantially contributed to the clarification of the hemispheric organization of cognitive, motor, and sensory functions because it is based on a close coupling between regional CBF changes and neural activation [4][5][6][7]. Due to a pulsewave Doppler technology and continuous registration of CBF in cerebral basal arteries, FTCD offers an excellent temporal resolution in comparison to other neuroimaging techniques [8,9]. Although different in nature from other neuroimaging procedures and accordingly limited for spatial resolution, TCD offers the advantage of being noninvasive and repeatable as clinically indicated [10].…”
Section: Introductionmentioning
confidence: 99%